Identifying and reaching Japanese tourists coming to Ha Giang provinc - Bien, Thi Thuy Duong (H. : ĐHQGHN, 2020)
This study will contribute to the improvement of tourism not only in in Ha Giang province but also for other provinces or tourist destination in Vietnam as a reference to attract Japanese tourists. This research will encourage Ha Giang province to be drawn to consider Japan as the target market as well as finding others target markets to concentrate on. Moreover, this study can also help travel agencies in Vietnam have a closer look on the characteristics of Japan’s market and its potential.